Experimental evidences of radicals production by hydrodynamic cavitation: a short review - Nöpel, Julius-Alexander; Ayela, Frédéric (Comptes Rendus. Chimie, 2023)
The presence of induced radicals and of chemical reactions, in liquids processed in ultrasonic reactors producing acoustic cavitation, has been widely demonstrated and is known as sonochemistry. Otherwise, the number of publications related to chemical reactions caused by hydrodynamic cavitation arising in a liquid flowing out, is more limited. Most of these articles have exposed qualitative results and empirical attempts in order to increase a primary weak efficiency. As the physics of collapsing bubbles in a flow is more complex than the monitoring of acoustic bubbles at a fixed frequency, it was largely assumed, until shortly, that hydrodynamic cavitation has inherent limitations preventing from getting relevant radical yields. However, new efforts have been recently performed to evolve from qualitative to quantitative measurements, in order to be able to know whether hydrodynamic cavitation could become a reliable process for wastewater treatment or not. This short review focuses on recent progresses that have made possible experimental evidences of radical production in hydrodynamic cavitation, and on forthcoming orientations.